Six Oligosaccharides’ Variation in Breast Milk: A Study in South China from 0 to 400 Days Postpartum - Shuang Liu (MDPI AG, 2021)
This study investigated the variation in oligosaccharide levels in the breast milk of south Chinese mothers in a prolonged breastfeeding period of up to 400 days postpartum. A total of 488 breast milk samples were collected from 335 healthy mothers at five different time points: 0–5 days, 10–15 days, 40–45 days, 200–240 days, and 300–400 days postpartum. A high-performance anion-exchange chromatography-pulsed amperometric detector (HPAEC-PAD) was used to quantify 2′-fucosyllactose (2′-FL), 3-fucosyllactose (3-FL), lacto-N-tetraose (LNT), lacto-N-neotetraose (LNnT), 3′-sialyllactose (3′-SL) and 6′-sialyllactose (6′-SL). In this study, we found six oligosaccharides that were present in breast milk from 0 to 400 days postpartum. The median value ranges of individual oligosaccharide components in this study were 1013–2891 mg/L 2′-FL, 193–1421 mg/L 3-FL, 314–1478 mg/L LNT, 44–255 mg/L LNnT, 111–241 mg/L 3′-SL, and 23–602 mg/L6′-SL. HMO levels decreased over the lactation periods, except for 3-FL, which increased throughout lactation. The predominant fucosylated and sialylated HMOs were 2′-FL and 6′-SL at 40–45 days postpartum and changed to 3-FL and 3′-SL at 200–240 days postpartum. Results from this study showed that lactating women continue to provide their offspring with a high level of 2′-FL one year after delivery, suggesting that 2′-FL may play an important role for infants in early life. Our findings also provide further evidence in support of breastfeeding after one-year postpartum.